Diagnostic accuracy of hysteroscopy vs dilation and curettage (D&C) for atypical endometrial hyperplasia in patients performing hysterectomy or serial follow-up - Luigi Nappi; Stefano Angioni; Vincenzo De Feo; Pantaleo Greco; Guglielmo Stabile; Francesca Greco; Maurizio Nicola D'Alterio; Felice Sorrentino (Clinical and Experimental Obstetrics & Gynecology)
Background: Endometrial hyperplasia (EH) is considered a heterogeneous pre-neoplastic clinical entity characterized by an abnormal glandular proliferation, with less than half of the tissue area occupied by the stroma. The aim of this retrospective study was to evaluate the correlation between the histological diagnosis of atypical endometrial hyperplasia (AEH) obtained through office hysteroscopy (OH) or uterine dilation and curettage (D&C) and the definitive histological evaluation after hysterectomy. Methods: Among 112 patients with atypical EH, 45 (40%) underwent hysteroscopy and 67 (60%) curettage. Results: The diagnostic accuracy of OH was very high: in particular, it showed a diagnostic coincidence in 87% of cases with the definitive histological diagnosis through hysteroscopy. The curettage, instead, had diagnostic coincidence only in 14% of cases. Conclusion: Office hysteroscopy is the ideal procedure for both diagnosis and follow-up of endometrial hyperplasia.